2007
DOI: 10.4314/thrb.v9i2.14315
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and visual impairement in Atakunmosa west local government area of southwestern Nigeria

Abstract: Blindness survey remains a useful tool for eye care needs assessment. A cross sectional survey of Atakunmosa West Local Government Area, a rural community of southwest Nigeria with no form of eye care facility was carried out. The objective of this study was to define areas of eye care need and develop programme for elimination of avoidable blindness in the region. Multistage cluster sampling technique selected 1,248 respondents across all the eleven health districts. Respondents had visual acuity and ocular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 11 publications
3
24
5
1
Order By: Relevance
“…Observing data from other Brazilian regions and developing countries, the prevalence of blindness from cataract in the general population is much higher than what was seen here, with 1.49% in the metropolitan region of São Paulo (10) , 2.11% in a Brazilian indigenous group from Amazonia (11) , 2.61% of the whole population in Cambodia (2) ; 4.26% in Nigeria (12) ; 1.17% of the over 50 population in Ruanda and Kenya (13) ; and 2.01% of over 50's in Paraguay (14) . Compared to other Latin American countries, our data is similar to the metropolitan area of Buenos Aires that has 0.5% of bilateral blindness caused by cataract (15) .…”
Section: Discussioncontrasting
confidence: 60%
“…Observing data from other Brazilian regions and developing countries, the prevalence of blindness from cataract in the general population is much higher than what was seen here, with 1.49% in the metropolitan region of São Paulo (10) , 2.11% in a Brazilian indigenous group from Amazonia (11) , 2.61% of the whole population in Cambodia (2) ; 4.26% in Nigeria (12) ; 1.17% of the over 50 population in Ruanda and Kenya (13) ; and 2.01% of over 50's in Paraguay (14) . Compared to other Latin American countries, our data is similar to the metropolitan area of Buenos Aires that has 0.5% of bilateral blindness caused by cataract (15) .…”
Section: Discussioncontrasting
confidence: 60%
“…Sample size for the study was determined using EPI INFO V6 statistical software. Accepting a 95% confidence level, a blindness prevalence rate of 1.1% [9] actual population figure of 159,114 [10] for the communities in the Local Government Area, an acceptable error margin of 0.5% and a design effect of 1.2, a minimum sample size of 1,382 was calculated. This Local Government is composed of 13 rural communities with 449 enumeration areas.…”
Section: Methodsmentioning
confidence: 99%
“…Driving cessation, regardless of whether it is voluntary or involuntary (example, license revocation), can have a number of adverse consequences such as decreased health-related quality of life, increased likelihood of depression & social isolation and reduced access to healthcare services (3). Comprehensive routine eye care and maintaining good eye care practice is an important part of the health care process that should be adopted by drivers (4). It is an important practice regardless of your age, occupation or your physical health (5).…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, most research has revealed age 50 years and below as the mean age of commercial drivers, so this explains how important routine eye check is for drivers (7). Unfortunately, practice of routine eye check is rare in developing countries where the level of illiteracy and poverty is averagely high (4,8).…”
Section: Introductionmentioning
confidence: 99%